Effectiveness of an Educational Program on Nurses’ Knowledge towards Physical Therapy for Patients with COVID-19 - Qasim Dali Mohammed, Hussein Hadi Atiyah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Traditional Chest Physical Therapy is a method of respiratory therapy in which the lungs are drained using an airway clearance technique; it consists of placement, drainage, and percussion. Techniques have been developed, as a result, new techniques emerged that facilitated secretion removal and even included strategies for increasing lung capacity and volume. Objectives: This study aims to evaluate the effectiveness of an interventional program on nursing staffs’ knowledge toward physical therapy for patients with COVID-19. Methodology: A pre-experimental (one-pretest-posttest) design was used to conduct this study. A non-probability (purposive) sampling was used to select (60 nurses) working in ICU. To measure the effectiveness of the interventional program, the researcher used a knowledge form that included (22) questions patient-oriented with COVID-19. The validity of the questionnaire and the interventional program was verified by presenting it to (12) experts. The reliability was determined using the test-retest approach for the knowledge questionnaire. Data analysis was done using the Statistical Package of Social Sciences (SPSS) version 25. Results: The study findings showed that there are highly statistically significant differences between the scores of nursing staffs’ knowledge in two levels of measurements (pre-test and post-test) at p-value (0.000), where the statistical mean of the overall knowledge of nursing staff in the pre-test was (1.657), while it becomes (12.297) in post-test, after the interventional program has been applied. Conclusion: The study concluded that the interventional program positively affects the nursing staffs’ knowledge concerning physical therapy for patients with COVID-19.